Penerapan Digital Marketing pada Penjualan Karang Hias (Ornamental Coral): Studi Kasus pada CV. Rezky Bahari Makassar - Burhan Burhan; Sumarni Sumarni; Rahmayati Rahmayati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
In today's digital era, the application of digital marketing is the main key in increasing the sales volume of various products, including ornamental corals. This research aims to find out how CV Rezky Bahari Makassar applies digital marketing to increase sales of ornamental corals. Through a qualitative approach of exploratory case study type, data collection through interviews, observation, and documentation. data analysis methods using descriptive qualitative. The results showed that CV. Rezky Bahari Makassar has implemented various digital marketing strategies, including social media marketing, such as WhatsApp, Facebook, Instagram, Website and Email Marketing, Integrated digital marketing strategies focus on attractive visual content, technological innovations such as 360-degree videos and direct interaction with customers to increase the visibility and accessibility of its products to consumers. The implementation of this strategy resulted in a significant increase in sales of ornamental corals. Despite facing challenges such as a decline in revenue due to the Covid-19 pandemic in 2020, the company managed to return to a positive growth path through digital marketing strategies, with sales revenue reaching its highest peak in 2023. This research provides insights into effective digital marketing practices in the ornamental coral industry and suggests that the integration of various digital channels can result in increased sales.